Analysis of the Effects of the Indian Ocean Dipole (IOD) and the Madden-Julian Oscillation (MJO) on Rainfall During the Dry Season in Padang - Endar Sabila; Nofi Yendri Sudiar; Hamdi; Letmi Dwiridal (Darul Yasin Al Sys, 2026)
Dry-season rainfall in Padang is highly variable and can reach extreme intensities; however, the influence of global atmospheric phenomena on rainfall variability during June–August (JJA) remains insufficiently understood. This study examined the relationships of the Madden–Julian Oscillation (MJO) and Indian Ocean Dipole (IOD) with dry-season rainfall variability in Padang. The analysis used daily MJO index data from the Bureau of Meteorology, monthly Dipole Mode Index data from JAMSTEC, and rainfall records from Minangkabau International Airport Station for 1991–2020 and Teluk Bayur Maritime Meteorological Station for 1994–2020. Pearson correlation and cross-correlation analyses were employed to determine the strength, significance, and temporal lag of the relationships between MJO and IOD activity and rainfall. MJO Phase 3 was positively and significantly correlated with JJA rainfall at Minangkabau International Airport Station (r = .254, p = .003) and Teluk Bayur Station (r = .232, p = .006), whereas MJO Phase 4 showed no significant relationship. Cross-correlation analysis identified a significant negative relationship at a lag of approximately 10–12 days, indicating that rainfall tends to decrease 10–12 days after the active MJO passes. By contrast, the negative IOD was not significantly associated with JJA rainfall in either the contemporaneous or lagged analyses. These findings demonstrate that MJO Phase 3 is more closely associated with dry-season rainfall variability in Padang than either MJO Phase 4 or the negative IOD. Monitoring MJO Phase 3 may therefore provide useful supplementary information for medium-range dry-season rainfall forecasting in the region.